Management Attempts to Avoid Accounting Disclosure Oversight: The Effects of Trust and Knowledge on Corporate Directors’ Governance Ability - Rose, Anna M. (Journal of business ethics, 2008)
Management has the opportunity to promote self-serving accounting practices, such as earnings management, when management can effectively avoid oversight by the audit committee. This article investigates the effects of financial knowledge and dispositional trust on the ability of audit committee members to recognize management attempts to avoid full disclosure to the board and potentially deceive board members. The results of a controlled laboratory experiment with 40 experienced audit committee member participants indicate that: (1) Audit committee members with less financial knowledge are more likely to accept insufficient client explanations for accounting judgments than are more knowledgeable audit committee members; (2) Audit committee members with less financial knowledge are more likely to reject sufficient client explanations for accounting judgments than are more knowledgeable audit committee members; and (3) Audit committee members that place higher levels of trust in others are more likely to accept insufficient client explanations for accounting judgments than are less trusting committee members.